Advanced nutrition and human metabolism - Gropper, Sareen Annora Stepnick; Smith, Jack L. (Belmont, Massachusetts : Wadsworth/Cengage Learning, 2013)
Covers the biochemistry of vitamins, minerals, and energy nutrients. This title examines the structure and function of water-soluble and fat-soluble vitamins and their regulatory role in metabolism, looks at electrolyte and fluid balance, and covers the role of nutrition in the development or exacerbation of chronic disease
1. The cell: a microcosm of life -- 2. The digestive system: mechanism for nourishing the body -- 3. Carbohydrates -- 4. Fiber -- 5. Lipids -- 6. Protein -- 7. Integration and regulation of metabolism and the impact of exercise and sport -- 8. Body composition, energy expenditure, and energy balance -- 9. Water-soluble vitamins -- 10. The fat-soluble vitamins -- 11. Major minerals -- 12. Water and electrolytes -- 13. Essential trace and ultratrace minerals -- 14. Nonessential trace and ultratrace minerals
Includes bibliographical references and index
Keywords: Metabolism; Nutrition; Metabolism; Nutritional Physiological Phenomena